Morphological features and distribution of Trichinella sp. larvae in the muscles of the lynx - O. B. Zhdanova; I. I. Okulova; B. E. Zarubin; I. A. Domsky; A. V. Uspensky; L. A. Napisanova; D. V. Rossokhin (Российский паразитологический журнал, 2021)
The purpose of the research is determination of optimal muscle tissue areas for confirmation of diagnosis in the lynx by trichinelloscopy.Materials and methods. The distribution of Trichinella sp. larvae were studied in spontaneously infected lynxes by the trichinelloscopy method when examining 72 sections in a compressorium. In addition to calculating the total number of isolated larvae and the percentage in muscles, we recalculated per 1 g of animal muscles and performed morphometry of the area and perimeter of Trichinella sp. capsules from various muscles, and calculated the ratio of the capsule length and width, and the M value (arithmetic mean): the area of the capsule and its perimeter. We determined the percentage ratio of the larva size to the capsule and the position in the myosymplast using the Vision Bio system (Epi 2014). The results were statistically processed using the Microsoft Excel software package. The larvae were photographed directly from the screen with digital signal processed by the Vision Bio system (Epi 2014).Results and discussion. It has been found that the capsules in the muscles are more often rounded (90% of all Trichinella sp. have a length-to-width ratio of 1.1 : 1). However, there are also oval capsules, the largest number of which was recorded in the masticatory muscles (33% of the total capsules in the masticatory muscles). When studying the selective expansion of larvae, it was found that the masticatory muscles, tongue, diaphragm and gastrocnemius muscles were the most populated. Conclusion. We identified high prevalence and intensity of infection in the lynx, which indicates not only the epizootic significance of the lynx in the spread of trichinellosis in the Kirov Region, but also its epidemiological significance as a source of infection. Due to the fact that the meat of this animal is eaten and there is a risk of human infection, it is necessary to examine the carcasses of these animals for trichinellosis by the compressor trichinelloscopy method or by the peptolysis method.